2021
DOI: 10.1021/acs.analchem.1c02402
|View full text |Cite
|
Sign up to set email alerts
|

How Narrow Is the Gas Phase Mobility Distribution of Enveloped Viruses? The Case of the Φ6 Bacteriophage

Abstract: We use the Φ6 bacteriophage previously exploited as a BSL-1 surrogate of severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome (MERS) coronavirus to obtain the first high-resolution gas phase mobility spectra of an enveloped virus. The relative full width at half-maximum found for the viral mobility distribution (FWHM Z < 3.7%) is substantially narrower than that reported by prior mobility or microscopy studies with other enveloped viruses. It is nevertheless not as narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Whatever its cause, the mismatch between the sizes determined by electron microscopy and the mobility is not unique to our study. Comparable differences have been found by Fernandez de la Mora et al, who report a mobility diameter of 63.7 nm for the enveloped bacteriophage Φ6, for which microscopy measurements had previously given 75 nm. A study relying on mobility as well as several microscopy techniques has found similar differences, with a mobility diameter always smaller than the microscopy value.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Whatever its cause, the mismatch between the sizes determined by electron microscopy and the mobility is not unique to our study. Comparable differences have been found by Fernandez de la Mora et al, who report a mobility diameter of 63.7 nm for the enveloped bacteriophage Φ6, for which microscopy measurements had previously given 75 nm. A study relying on mobility as well as several microscopy techniques has found similar differences, with a mobility diameter always smaller than the microscopy value.…”
Section: Discussionmentioning
confidence: 48%
“…This presumed double compaction would, on the one hand, be driven by capillary stresses arising in the gas phase and would, on the other hand, be enabled by the partially empty SLP interior (not all inner space is occupied by the viral genome). Such collapses are common in thin shells under stress and have been invoked in biophysical modeling of viral capsids. ,, In a forthcoming study, we will argue that empty capsids often buckle in the gas phase into a broad range of shapes, resulting in a broad mobility distribution (i.e., the satellite peak in Figure a). The notion that our gas-phase structures have undergone a partial collapse yet have narrow mobility distributions therefore requires some explanation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The bacteriophage Phi6 (Φ6) was used as a BSL-1 surrogate organism to estimate the rate of uptake of virus-laden aerosols by PDMS. ,, Φ6 has previously been explored as a surrogate for various enveloped viruses in environmental exposure and persistence studies , and was recently utilized as a surrogate for SARS-CoV-2 because its physiological characteristics are similar to those of the virus, including a diameter ranging from 75 to 100 nm (vs a diameter of 90–110 nm for SARS-CoV-2), a spherical shape with protruding spike proteins, a lipid envelope, and an RNA genome. ,,, …”
Section: Methodsmentioning
confidence: 99%
“…The bacteriophage Phi6 (Φ6) was used as a BSL-1 surrogate organism to estimate the rate of uptake of virus-laden aerosols by PDMS. 10,26,27 Φ6 has previously been explored as a surrogate for various enveloped viruses in environmental exposure and persistence studies 10,28−30 and was recently utilized as a surrogate for SARS-CoV-2 because its physiological characteristics are similar to those of the virus, including a diameter ranging from 75 to 100 nm (vs a diameter of 90−110 nm for SARS-CoV-2), 31 a spherical shape with protruding spike proteins, a lipid envelope, and an RNA genome. 10,26,32,33 Rotating Drum Configuration, Aerosol Generation, and Aerosol Sampling.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%